2003
DOI: 10.1291/hypres.26.669
|View full text |Cite
|
Sign up to set email alerts
|

Role of Insulin Resistance in Nondipper Essential Hypertensive Patients

Abstract: of atrial and brain natriuretic peptides (ANP and BNP) in patients with essential hypertension (7-9). Accumulating evidence suggests that insulin resistance plays an important role in the development of essential hypertension (10, 11). Therefore, we hypothesized that LVH with concomitant increase in plasma concentrations of ANP and BNP may occur more easily in nondipper essential hypertensive patients than in dippers, and that insulin resistance may play an essential role in these processes. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 30 publications
5
44
1
1
Order By: Relevance
“…is similar to those observed by Anan et al 12 , who emphasized the importance of the method chosen for the investigation of hypertensive patients.…”
Section: Dm -Diabetes Mellitus; MI -Myocardium Infarction; Dlp -Dislisupporting
confidence: 90%
See 4 more Smart Citations
“…is similar to those observed by Anan et al 12 , who emphasized the importance of the method chosen for the investigation of hypertensive patients.…”
Section: Dm -Diabetes Mellitus; MI -Myocardium Infarction; Dlp -Dislisupporting
confidence: 90%
“…After the analysis of sociodemographic factors, we pointed out in our sample the absence of association between ND and the remaining variables (age, SAH time, school degree, waist circumference, genre, race, smoking and sedentarism), which was confirmed by other studies 12,14,15,26 . Other authors observed that individuals without ND were older 16,18,19 and that this condition occurs preferentially in non-white people 19 .…”
Section: Dm -Diabetes Mellitus; MI -Myocardium Infarction; Dlp -Dislisupporting
confidence: 87%
See 3 more Smart Citations